Indulgence and Long Term Orientation Influence Prosocial Behavior at National Level - Guo, Qingke; Liu, Zhen; Li, Xile; Qiao, Xiuqing (Frontiers in Psychology, 2018)
The relationships between several Hofstede’s cultural dimensions and prosocial behavior at national level have been investigated by some studies. Yet the roles of indulgence versus restraint (IVR) and long-term versus short-term orientation (LTO), two newly established cultural dimensions, have received insufficient interest. This study was aimed to investigate whether the World Giving Index (WGI), a national level measure of prosocial behavior (including donating, volunteering, and helping a stranger) provided by Gallup, was affected by IVR and LTO. The results suggested a positive link between IVR and WGI, and a negative link between LTO and helping a stranger. Culture values can in a great extend account for why prosocial behavior varies across countries. Further analysis revealed interactions among IVR, LTO, and individualism versus collectivism (IND). Simple slope analyses found that: (1) a higher level of IND could enhance the positive influence of IVR on prosocial behavior; (2) a lower level of IND could weaken the negative impact of LTO on prosocial behavior; (3) a higher level of IVR could weaken the negative effect of LTO on prosocial behavior.